(untitled) (Cardiovascular Journal, 2012)
Background: Data of stent patency or the development of ISR in multiple or overlapping stent in a single vessel territory of Bangladeshi diabetic (DM) patient population is not yet available. Therefore, the aim of our present study was to assess primarily the long-term stent patency of varieties of stent in patient with Diabetes Mellitus (DM) and Non-diabetes Mellitus (NDM). Methods: Patients were prospectively selected from, who underwent coronary angiogram at our hospital for further evaluation of their previous PTCA in the e36 months preceding the study for the quantifying period of 2007-2011. Total 51 (11%) patients (male: 41, Female: 10) from a total 461 patients were included in this study who has multiple or overlapping stent in single vessel territory. Total 32 (62.7%) patients included into the DM group with an average age of 57 yrs and in the NDM were 19 (37.3%) with 58 yrs. Average ISR period was 3.1 ± 2.4 yrs. Results: Our result shows that total 70 stent were deployed in 33 vessels of DM patient and 44 stent in 21 vessel of Non-DM patient. Territory wise total number of deployed stent in patient of DM: NDM were in LAD 34 (48.6%): 18(41%), RCA 16 (22.8%): 4 (9%) and LCX 20(28.6%): 22(55%). Stent used in DM: NDM; were BMS 21 (30%): 22(50%), Sirolimus 24(34.3%): 10(22.7%), Paclitaxel 17(24.3%):8(18.2%), Everolimus 6(8.6%):4(9.1%)%). Re-look coronary angiogram (CAG) revealed that increased number of in-stent restenosis occurred more in patient with Diabetes [DM 10(31.3%) vs NDM 5(26.3%)]. Significant ISR (ISR>60%) in DM patient treated with for BMS were 4 (36.4%), for Paclitaxel 3(42.3%), for Sirolimus 1(9.1%). Average stent size and length were almost same in both groups for any coronary territory. Conclusion: Our study has revealed that increased number of ISR were more in patient with diabetes (DM) in a single artery territory when multiple stents were used either separately or as overlapping. Among the stent used, Sirolimus shows better patency with reduced ISR than Paclitaxel and other limus eluting stent for an average period of follow up of 3.1 yrs. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12208 Cardiovasc. j. 2012; 5(1): 18-22